Magnetoelastic effects in Europium Chalcogenides - Majid, Abdul Muhammad (My University, 1975)
The theory of magnetoelastic interactions is described for ferromagnetic crystals with cubic symmetry and is applied to the europium chalcogenide series. The expressions for the change of elastic constants as a function of applied magnetic field are written down. Using available data on anisotropy and magnetostriction, the crystal field parameters and the magnetoelastic constants are estimated for europium oxide. The fractional change in the measured elastic constant C44 is predicted to be 5x10^-4 in an applied field of 25 k0e.
Keywords: Physics; Physics